Fiscal reform, long-run growth and welfare in a monetary model: The case of Mexico - Sarabia, Arturo Antón (Estudios Económicos de El Colegio de México, 2005)
A neoclassical endogenous growth model is presented where a representative household deriving utility from both consumption and leisure must use money in order to purchase consumption goods. Taxes on money holdings, capital and labor income may be used to finance an exogenous stream of wasteful government expenditures. The model is especially calibrated for the Mexican economy and used to analyze the effect of alternative tax reforms and higher government expenditure levels on both growth and welfare.